ANALYSIS CARBOHIDRATE CONTENT AS AN ALTERNATIF TO HALAL FOOD IN NATA JACKFRUIT - Latif, Ulfa Triyani A; Hamina, Hamina; Hafsan, Hafsan; Anwar, Zulfahri (Universitas Islam Negeri Alauddin Makassar, 2022)
.